(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
The current research dealt with two pivots, the first is the effect of dissolving Parliament on the legislative authority and the second is the effect on the executive authority. The researcher talked about the nature of the relationship between the dissolution of Parliament and the effect on the executive and legislative authorities through a number of hypotheses. The goal of the researcher is to identify the impact of the dissolution and the consequences of dissolving the two authorities, including taking the entire parliament’s authority away, or keeping the parliament with full powers until a new parliament is convened. As well as stripping the powers of the government and making it a caretaker government or a government with full powers until a new government is chosen and its impact on the performance of both authorities. The researcher has adopted the descriptive analytical approach because it is the most appropriate to know the reality of the research aspects. Iraq and Lebanon were chosen for the purpose of highlighting the political system in these two countries. The researcher has reached many results, the most prominent of which is the dissolution of Parliament in Iraq, which makes the government a government that handles daily matters, and the government’s survival of managing daily matters is impotent and robbed of its powers. Especially since the legislator did not make an appropriate limit or a specific effect in the event that the government is not formed. The researcher also reached many recommendations, the most important of which is that Article 64 of the Iraqi constitution for the year 2005 must be addressed and the results of the dissolution should be that the government exercises full powers until a new government is formed.